2021
DOI: 10.1002/sd.2264
|View full text |Cite
|
Sign up to set email alerts
|

Achieving sustainable development goals through board size and innovation

Abstract: Sustainable development is one of the prominent goals promoted by the United Nations (UN). To achieve Sustainable Development Goals, the UN identifies innovation as one of the important elements. Motivated by this, we explore how board size affects firm's innovation and find a negative relation between board size and firm's innovation. Our analyses including ordinary least squares (OLS) regressions, instrumental variable, propensity score matching, and generalized method of moment (GMM) dynamic panel data esti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 151 publications
1
37
0
1
Order By: Relevance
“…In addition, the resource dependence theory explains that the board has a role to offer critical resources to the firm including legitimacy and counsel (Hillman & Dalziel, 2003). As a board needs both capabilities and experience to effectively exercise its monitoring function through evaluating management, and assessing corporate strategies and social responsibility (Hillman & Dalziel, 2003), it is commonly agreed that board characteristics have a significant impact on firm behavior and performance (e.g., Chindasombatcharoen et al, 2021; Zubeltzu‐Jaka et al, 2020). Many studies found that the background and experience of board members were very important for effective monitoring (Carpenter & Westphal, 2001) and stakeholder engagement (Fernández‐Gago et al, 2018).…”
Section: Review Of Related Literaturesmentioning
confidence: 99%
“…In addition, the resource dependence theory explains that the board has a role to offer critical resources to the firm including legitimacy and counsel (Hillman & Dalziel, 2003). As a board needs both capabilities and experience to effectively exercise its monitoring function through evaluating management, and assessing corporate strategies and social responsibility (Hillman & Dalziel, 2003), it is commonly agreed that board characteristics have a significant impact on firm behavior and performance (e.g., Chindasombatcharoen et al, 2021; Zubeltzu‐Jaka et al, 2020). Many studies found that the background and experience of board members were very important for effective monitoring (Carpenter & Westphal, 2001) and stakeholder engagement (Fernández‐Gago et al, 2018).…”
Section: Review Of Related Literaturesmentioning
confidence: 99%
“…However, the achievement of the Sustainable Development Goals (SDGs) comes with significant challenges (Grover et al, 2018). The studies carried out show that progress is being made towards achieving the SDGs (Chindasombatcharoen et al, 2021; Haughton & Keane, 2021; Lyytimäki et al, 2020; Sanchez‐Planelles et al, 2022), but neither the speed nor the scale are adequate to improve the current levels of poverty, hunger, education, and health that characterize certain territories as well as to reduce climate emergency or discrimination (United Nations, 2019, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…However, information on corporate R&D investments are usually opaque by nature and this gives rise to agency issue between the management who is responsible for making the R&D investments and the stakeholders of the firm. Good corporate governance has shown to mitigate the agency issue (e.g., Chindasombatcharoen et al, 2021). An aspect of governance that can both address the agency issue and information opaqueness issue is blockholders—owners who have substantial holdings in the firm.…”
Section: Discussionmentioning
confidence: 99%
“…The literature underlines various factors that are instrumental in promoting innovation as well as creating value in firms. Among those factors are the institutional context (Tabrizian, 2019), owners (Pucheta‐Martinez & Chiva‐Ortells, 2018; Timur & Timur, 2015), and firm‐level governance structure (Chindasombatcharoen et al, 2021; Martinez‐Ferrero & Garcia‐Meca, 2020; Pucheta‐Martinez et al, 2019).…”
Section: Introductionmentioning
confidence: 99%